2009
DOI: 10.1044/1092-4388(2008/07-0238)
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Text Type, Topic Familiarity, and Stuttering Frequency on Listener Recall, Comprehension, and Mental Effort

Abstract: Stuttering has a greater influence on listener recall and comprehension for narrative than for expository texts. Topic familiarity affects free and cued recall but has no influence on story comprehension. Regardless of the amount of stuttering, mental effort was high for both text types and levels of familiarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Regardless of the cause, speech disfluency can be problematic for the listener, requiring greater effort to process and resulting in poorer recall of messages (Panico & Healey, 2009) and making speakers vulnerable to losing their conversational turn (Perkins, 1995). Self-corrections may be justified if they improve the eventual communicative message.…”
Section: Disfluency In Aphasia and Aosmentioning
confidence: 99%
“…Regardless of the cause, speech disfluency can be problematic for the listener, requiring greater effort to process and resulting in poorer recall of messages (Panico & Healey, 2009) and making speakers vulnerable to losing their conversational turn (Perkins, 1995). Self-corrections may be justified if they improve the eventual communicative message.…”
Section: Disfluency In Aphasia and Aosmentioning
confidence: 99%
“…People with voice disorders (and their speech-language pathologists) may be concerned that what they say is remembered less well than what people without voice disorders say. There is a basis for this concern, as it has been found that the speech of people with other speech-language disorders, such as stuttering, is remembered less well [ 25 ]. The current findings help to alleviate this concern, as total memory was not significantly hindered by a moderate-to-severely disordered voice.…”
Section: Discussionmentioning
confidence: 99%
“…Okutulan kitap diğer kitaplarla çağrışımı yapılırken sadece kitapların türüne değil aynı zamanda işlenen konu açısından da çağrışımlar yapıldığı görülmektedir. Bir kitabın ya da eserin konusu okuyucu/izleyiciyi etkileyen önemli etkenlerin başında gelmektedir (Recht ve Leslie, 1988;Panico ve Healey, 2009;Charzyńska, 2015). Yalnız Efe adlı kitap öğrencilere İnce Memed, Hüseyin Rahmi Gürpınar Gulyabani, Efsane Kadın Nene Hatun, Başını Vermeyen Şehit, Ahmet Rasim -Falaka, Prenses Mulan, Ömer Seyfettin'in Keramet Öyküsü, Ant, Suç ve Ceza adlı kitaplar ile Süt Kardeşler, Kertenkele, Kara Peçe, Scooby Doo, Hababam Sınıfı ve Fury(öfke) filmlerini çağrıştırmıştır.…”
Section: Tartişma Ve Sonuçunclassified